Teong Negeri: Sentralitas Folklore Nama Lokal Komunitas dalam Jejaring Sosio-Kultural Islam Kristen di Maluku - Revaldo Pravasta Julian Mb Salakory; Izak Yohan Matriks Lattu; Rama Tulus Pilakoannu (Universitas Andalas, 2020)
This article analysis about Teong Negeri has folklore centrality of community local name of Muslim-Christian socio-cultural network in Maluku. This study is qualitative research. Data were collected through interviews, documentary studies an observation. Methods analysis employed was descriptive qualitative. In the folklore of the village Wassu of Erihatu Samasuru (Christian), it has pela of the village of Haya Nakajarimau (Muslim) which means leader (older brother) for his three brothers, the village of Hatu Silalou (Christian) and the village of Tehua Lounusa Amalatu (Muslim). Communal narratives bind and become a link to give spirit to identity because society listens to local stories about Teong Negeri that have strong meanings, believing in each other. The four villages, in central Maluku, which are Wassu, Haya, Hatu, and Tehua, use the Teong Negeri symbol as an identity to maintain relations of kinship bond. The network that was built was challenged when the religious communal conflict happened, but the spirit towards the culture was always unheld. Teong Negeri became a symbol of central identity towards the traditional village that was able to regulate the socio-cultural system of every village in Maluku. not only for every community that has a bond of brotherhood or ethnicity. However, it becomes a universal symbol when, as a socio-cultural capital that is able to bridge the community from outside (buton migrants) based on cross-generation dialogue carried out by early generations of indigenous Maluku people with Buton migrants (migrants) in Maluku in order to have knowledge about the relationship harmonious.